Promoter Methylation Regulates Estrogen Receptor 2 in Human Endometrium and Endometriosis - Xue, Qing; Lin, Zhihong; Cheng, You-Hong; Huang, Chiang-Ching; Marsh, Erica; Yin, Ping; Milad, Magdy P; Confino, Edmond; Reierstad, Scott; Innes, Joy; Bulun, Serdar E (Biology of reproduction, 2007)
Steroid receptors in the stromal cells of endometrium and its disease counterpart tissue endometriosis play critical physiologic roles. We found that mRNA and protein levels of estrogen receptor 2 (ESR2) were strikingly higher, whereas levels of estrogen receptor 1 (ESR1), total progesterone receptor (PGR), and progesterone receptor B (PGR B) were significantly lower in endometriotic versus endometrial stromal cells. Because ESR2 displayed the most striking levels of differential expression between endometriotic and endometrial cells, and the mechanisms for this difference are unknown, we tested the hypothesis that alteration in DNA methylation is a mechanism responsible for severely increased ESR2 mRNA levels in endometriotic cells. We identified a CpG island occupying the promoter region (-197/+359) of the ESR2 gene. Bisulfite sequencing of this region showed significantly higher methylation in primary endometrial cells (n = 8 subjects) versus endometriotic cells (n = 8 subjects). The demethylating agent 5-aza-2'-deoxycytidine significantly increased ESR2 mRNA levels in endometrial cells. Mechanistically, we employed serial deletion mutants of the ESR2 promoter fused to the luciferase reporter gene and transiently transfected into both endometriotic and endometrial cells. We demonstrated that the critical region (-197/+372) that confers promoter activity also bears the CpG island, and the activity of the ESR2 promoter was strongly inactivated by in vitro methylation. Taken together, methylation of a CpG island at the ESR2 promoter region is a primary mechanism responsible for differential expression of ESR2 in endometriosis and endometrium. These findings may be applied to a number of areas ranging from diagnosis to the treatment of endometriosis.